The Role of Political Parties in Communication at the Central and Regional Levels - Radian Syam (Green Publisher Indonesia, 2022)
Parties politics are one of the most important components of a country's political system. This article aims to generate the birth of political power through the political process in empowered institution state and through political communication from the middle to the grassroots. The research method used in this research is a descriptive qualitative method. The data types used in this research are qualitative data, which are divided into primary data and secondary data. Data sources obtained through library research techniques (library research) are related to resources available online and offline, such as: Scientific journals, books, and news from reliable sources. The findings of this study conclude that the role of political forces in the political system is crucial in the process of legislation and communication through which the party's vision and mission are realized. Political institutions that formally have legislative power are staffed by those empowered to do so, or are reflected in the power structure of state institutions through formal political power, such as the President, the Council of People's Representatives, and other state institutions and political infrastructure. Political power, such as political parties, community leaders, community organizations, NGOs, professional associations, etc.